2021
DOI: 10.1111/ppe.12836
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and preterm birth: A time‐stratified case‐crossover study in the San Joaquin Valley of California

Abstract: Background Air pollution is linked to preterm birth (PTB), but existing studies are primarily focused on chronic exposures, conducted in areas with moderate pollution, and/or subject to confounding. Objectives We investigated short‐term associations between two pollutants [particulate matter <2.5 microns (PM2.5) and ozone] and PTB, and estimated excess PTB cases potentially attributed to these pollutants. Methods This time‐stratified case‐crossover study includes 196,970 singleton pregnancies affected by PTB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
5
2
Order By: Relevance
“…[8][9][10][11] Conversely, the pandemic, particularly during the most extensive lockdowns, has resulted in less pollution and other adverse environmental factors that are considered to be potentially protective of preterm birth. [12][13][14] Nevertheless, the epidemiologic studies that have evaluated the relationship between the COVID-19 pandemic and preterm birth have had inconsistent results. Some have shown no change, some have shown a decreased risk, and some have shown an increased risk of preterm birth after the onset of the pandemic.…”
mentioning
confidence: 99%
“…[8][9][10][11] Conversely, the pandemic, particularly during the most extensive lockdowns, has resulted in less pollution and other adverse environmental factors that are considered to be potentially protective of preterm birth. [12][13][14] Nevertheless, the epidemiologic studies that have evaluated the relationship between the COVID-19 pandemic and preterm birth have had inconsistent results. Some have shown no change, some have shown a decreased risk, and some have shown an increased risk of preterm birth after the onset of the pandemic.…”
mentioning
confidence: 99%
“…In contrast, Ha and colleagues investigated the associations between short-term exposure to PM 2.5 and ozone (O 3 ) and preterm birth in the San Joaquin Valley, California, using a time-stratified case-crossover design. 4 A strength of using this study design is that adjusting for time-invariant factors, such as race/ethnicity, was not necessary in the statistical analysis. They found that PM 2.5 exposures at lag 5 and at lags 5-7 were associated with very preterm birth (gestational age <34 weeks) and early term birth (gestational age between 37 and 39 weeks), respectively, but associations were not found for preterm birth at any lags.…”
mentioning
confidence: 99%
“…Nevertheless, they found some associations between preterm birth and the summary measurement of PM 2.5 and diesel PM, from community mapping tools, indicating that places with higher levels | 91 SPECIAL ISSUE of PM 2.5 have greater risk for preterm birth. In contrast, Ha et al 4 focused on short-term pollutant exposures with lags up to seven days. The heterogeneous results by lag days indicated that exposure to PM 2.5 or O 3 is time-sensitive, but it is unclear why some specific lag days had positive associations with very preterm birth, whereas earlier lags (e.g., lag 1) did not.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most research on air pollution and preterm birth has focused on long‐term exposures (during the entire pregnancy or trimester‐specific exposure). Ha and colleagues 11 used a case‐crossover design to measure the extent to which acute air pollution exposure triggers preterm birth. This study design allows for identification of the health effects of acute exposures and inherently controls for time‐invariant confounding, as each participant with the outcome is compared with themselves at different time points.…”
mentioning
confidence: 99%